Developing English Learning through Android-Based Mobile Learning Method in Increasing Student Achievement In SMA 2 Subang - Mimin Aminah (Jurnal Mantik, 2022)
The development of information technology has brought a lot of changes in various sectors of human life, this is also followed by the development of mobile phones, which are increasingly different because they are driven by several important features in it, one of the operating systems that are often used on cellphones or smartphones in this era. now is android operating system. The operating system is the most important type of software, that's because on its part there are several important elements, especially in running programs and applications, besides that the operating system is also a part of the national education program curriculum with the hope of improving learning achievement in students. all student. Mobile learning is a new method that emerged thanks to the help of android systems, laptops, computers, to make it easier for students to access various learning materials, besides that mobile learning can also be accessed easily and practically and is not hampered by space and time. This study uses a descriptive method, with a quantitative approach, while the results of this study explain that in fact, teaching using technology and information media teaching materials as a new alternative in delivering various materials to students is indeed very appropriate, especially on subjects that are often complained of by students so that it gives results that are not optimal. The mobile learning method seems to be widely applied to English subjects, as is what happened in the SMA 2 Subang school environment, in order to keep up with the developments in the world of education which continues to experience changes in various things, the SMA 2 Subang school chooses the mobile learning method to be placed as one of the one of the driving factors in understanding various English language education materials, this is very reasonable considering the learning process that has been applied so far has not been able to be digested properly by all students, even it seems very boring.